Technoeconomic analysis of internal combustion engine – organic Rankine cycle systems for combined heat and power in energy-intensive buildings. (1st November 2019) - Simpson, Michael C.; Chatzopoulou, Maria Anna; Oyewunmi, Oyeniyi A.; Le Brun, Niccolo; Sapin, Paul; Markides, Christos N.
Highlights: Organic Rankine cycle engines are optimised for exhaust from stationary gas engines. Two configurations are assessed using energy usage data for thirty buildings. Use of jacket water increases power output by 20% but reduces project viability. System with condenser heat supplied to building shows 3.5- to 7.5-year payback. Abstract: For buildings with low heat-to-power demand ratios, the installation of internal combustion engines (ICEs) for the onsite provision of combined heat and power (CHP) results in large amounts of surplus heat. In the UK, such installations risk being ineligible for the CHP Quality Assurance (CHPQA) programme, thereby incurring additional levies. In this work, a technoeconomic optimisation of small-scale organic Rankine cycle (ORC) engines is performed, in which the ORC engines recover heat from the ICE exhaust gases in order to increase the overall efficiency of this combined solution and meet the CHPQA requirements. Two competing system configurations are assessed. In the first, the ORC engine also recovers heat from the CHP-ICE jacket water to generate additional power. In the second, the ORC engine operates at a higher condensing temperature, which prohibits jacket-water heat recovery but allows heat from the condenser to be delivered to the building. When optimised for minimum specific investment cost, the first configuration is initially found to deliver 20% more power (25.8 kW) at design conditions, and a minimum specific investment cost (1600 £/kW) that is 8% lower than the second configuration. However, the first configuration leads to less heat from the CHP-ICE being supplied to the building, increasing the cost of meeting the heat demand. By establishing part-load performance curves for both the CHP-ICE and ORC engines, the economic benefits from realistic operation can be evaluated. The present study goes beyond previous work by testing the configurations against a comprehensive database of real historical electricity and heating demand for thirty energy-intensive buildings at half-hour resolution. The discounted payback period for the second configuration is found to lie between 3.5 and 7.5 years for all of the buildings considered, while the first configuration is seen to recoup capital investment costs for only 23% of the buildings. The broad applicability of the second configuration offers attractive opportunities to increase manufacturing volumes and reduce unit costs. The findings are relevant to a range of buildings with heat-to-power demand ratios from 20% to 100%.